Loading regimen required to rapidly achieve therapeutic trough plasma concentration of teicoplanin and evaluation of clinical features - Seki M; Yabuno K; Miyawaki K; Miwa Y; Tomono K (Dove Medical Press, 2012)
Masafumi Seki,1,* Kaori Yabuno,1,2,* Koji Miyawaki,1,2 Yoshihiro Miwa,2 Kazunori Tomono11Division of Infection Control and Prevention, 2Department of Pharmacy, Osaka University Hospital, Suita, Osaka, Japan*These authors contributed equally to this workBackground: A trough concentration of >20 mg/L is considered the optimal dosage of teicoplanin required to ensure early therapeutic effects against methicillin-resistant Staphylococcus aureus (MRSA) infections including those in patients who develop febrile neutropenia after chemotherapy. This study determines appropriate initial doses during the first 2 days of administration and evaluates the therapeutic target teicoplanin trough concentration.Method: A 2-day regimen was evaluated in patients treated with 600 mg and 1200 mg or 1200 mg and 600 mg (total 1800 mg, Group 1), 800 mg and 800 mg (total 1600 mg, Group 2), and 800 mg and 400 mg (total 1200 mg, Group 3) of teicoplanin on Days 1 and 2, respectively. We also compared the efficiency and adverse effects at trough concentrations of 15–20 mg/L (Group A, n = 28) with >20 mg/L (Group B, n = 27) of teicoplanin, and also compared them with those on the similar concentrations of vancomycin (Groups C and D, n = 50 and 34, respectively).Results: The mean trough concentrations of teicoplanin on Days 4 or 5 were 22.2, 17.5, and 16.2 mg/L in Groups 1, 2, and 3, respectively. The clinical efficiency was 85.7%, 81.5%, 92.0%, and 91.5%, in Groups A, B, C, and D, respectively. The rates of adverse effects were not high in teicoplanin (nephrotoxicity, 7.1% and 3.7%, and hepatotoxicity, 14.3% and 11.1% in Groups A and B, respectively). However, more adverse effects tended to arise in patients who received vancomycin in nephrotoxicity (14.0% and 11.8%, in Groups C and D, respectively).Conclusion: These results suggest that the 2-day regimens with total 1800 mg achieved the most effective therapeutic trough plasma concentration of teicoplanin (20 mg/L). However, 15–20 mg/L might also be an effective trough target for initial teicoplanin treatment. These teicoplanin regimens might be safer in terms of renal function than vancomycin.Keywords: therapeutic drug monitoring, pharmacokinetics and pharmacodynamics, Staphylococcus aureus, MRSA, dosing regimen, adverse effect